(untitled) (Itinera, 2020)
This is a verse-essay in the form of six extended villanelles that discuss various aspects of the relationship between poetry, music, and the visual arts. More specifically they concern issues of ontology, autonomy, endurance, expressive power, and formal resistance to the vicissitudes of cultural change. The rhyme-scheme (tight but highly musical) is used to point up and differentiate the range of aesthetic attributes involved in this running debate.